Inequality, Reordering and Divergent Growth: Processes of Neighbourhood Change in Dutch Cities - Tal Modai-Snir; Maarten van Ham (Institute of Labor Economics (IZA), 2018)
The socio-economic mosaic of urban neighbourhoods changes under the influence of three distinctive distributional processes: reordering of the socio-economic position of urban neighbourhoods; changing levels of inequality between neighbourhoods; and an overall growth or decline in income levels which affects all neighbourhoods of an urban area. With the common practices in analysing neighbourhood change, the roles of these underlying processes are unclear. This paper builds on a decomposition method to analyse the roles of the three components of change in four largest Dutch city-regions. The results points to substantial variations in components of change in the four city-regions.
Keywords: O18; P25; R23; 330; neighbourhood change; socioeconomic change; income inequality; spatial polarisation; socio-spatial structure